THE FLEXIBILITY EVALUATION - CONSTRUCT THE REFERENTIAL TABLE TO KR BENCH (Fiep Bulletin - online, 2014)
The purpose of this study was to construct the referential table for the flexibility evaluation instrument - KR Bench. There were evaluating 4159 people, 3062 women and 1097 men. The data had been analyzed through the descriptive statistics, and distribution from gender, 6 classes of age (10 - 10 years) and 3 height levels (10 - 10 cm). This KR bench instrument and its classification table will be able to assist in studies with large populations and few resources, respecting the gender, age and height differences.
Keywords: evaluation instrument; classified table; flexibility